Ethical work climate in the national audit department offices in Malaysia - Ismail, Suhaiza; Yuhanis, Nursia (Accounting Research Institute (ARI), UiTM Shah Alam, 2019)
The study aims to examine the ethical work climate types of the National Audit Department (NAD) offices in Malaysia as perceived by the public sector auditors. The respondents of the study were public sector auditors in the NAD offices from both federal and state levels. Using a survey questionnaire comprising instrument about the ethical climate by Victor and Cullen (1988), a total of 382 responses was received and usable. In order to achieve the research objective, descriptive statistics of mean score and standard deviation were used. The results reveal that the highest mean score is ‘rules’ climate, indicating that the public sector auditors perceived this rules ethical climate to be highly present in their organizations. This is followed by ‘instrumental’ and ‘caring’ ethical climate types. In contrast, law ethical climate type was perceived as almost non-exist in the NAD offices. This study provides useful information on the types of ethical climate types that exist in the offices of the National Audit Department (NAD) as perceived by the public sector auditors which may to some extent help to inculcate the right ethical climate in order improve the level of ethics among public sector auditors which will subsequently enhance the credibility of the NAD and public trust in the government.